Therapy for elderly living in care centre by Planting Portulaca Grandiflora - Talib, Siti Salwa; Abu Bakar, Muhammad Radhi Rahimi; Shamsudin, Norsyaqina; Baharudin, Nursakinah; Ismail, Wan Ismahanisa; Mohd Nor, Mohamad Azhar (Universiti Teknologi MARA, Kedah, 2024)
Gardening has been reported to give a positive effect on the physical and psychology of people in golden age. This project aims to identify the feasibility of gardening by planting portulaca grandiflora in reuse bottles as a therapy for seniors living in the care centre, thirty-five (35) residents participated in the project. The resident age varies from 54 years old to 88 years old age. The feasibility measured based on observation on the surrounding and available resource in the centre and interviewing residents about the resource. The participants’ perception on gardening was evaluated using yes/no questionnaire pre and post gardening activity. The questions focus on interest, confidence, happiness, and commitment to look after the plant. The result shows in percentage an increase for all aspects, especially in the interest in and commitment to gardening as the basic need for success of garden therapy. The main issues identify is activity to water the plant as a residents stated exhausted. In conclusion, planting portulaca grandiflora is suitable choice for gardening yet research on additional resources needed to make it as a form of therapy and a safe leisure activity for elderly in the care centre.